Provisions, practices and performances of constitutional review in democratizing East Asia - Croissant, Aurel (The Pacific review, 2010)
This analysis of the institutional design and actual performance of constitutional review in five newly democratized nations in East Asia shows that during the last two decades the judiciary has come to play an increasingly important political role in South Korea, Taiwan and Indonesia. Constitutional courts in these three countries are more active in counterbalancing executive and legislative power than ever before. This however contrasts with the experiences of Thailand and Mongolia where constitutional courts were unable to fulfill a similar function. The discussion for potential explanations for this cross-national variance in court performance supports the critique in parts of the scholarly literature against purely institutional, cultural and structural explanations. Rather, the degree of political uncertainty and diffusion of political power are critical determinants for understanding why politicians comply with court judgments, or attempt to marginalize justices. In addition, the relationship between institutional support, compliance and the area of judicial review matters. In this regard, one lesson of the East Asian comparison is that a too early introduction of review of separation of power conflicts could actually make things worse, by threatening the court's authority and marginalizing its influence. This represents a danger often neglected in the democratization literature that claims judicial control of horizontal accountability mechanisms would necessarily help to consolidate democracy. (Pac Rev/GIGA)